IDENTIFICATION OF PRIORITY AREAS OF FOREIGN POLICIES OF THE MEMBER STATES OF THE EURASIAN ECONOMIC UNION IN THE FRAMEWORK OF BILATERAL COOPERATION - N. A. Efimova (Вестник университета)
The article is devoted to identifying priority areas of foreign policy of the Eurasian Economic Union (hereinafter – EAEU) member states in the framework of bilateral cooperation, reflected in national legal and other acts and documents, determining the main vector of the implemented foreign policy of each of the EAEU member states. As a result of the study, it has been concluded, that foreign policy issues are solved by each member of the EAEU independently. The lack of coordinated approaches to the implementation of the foreign policy activities of the EAEU member states, including in the framework of bilateral cooperation, cannot but affect the development of all economic integration. This mediates the need to model a coordinated approach to the implementation of the foreign policy of the EAEU member states as an integration unity, within the framework of which the interests of each EAEU member will be taken into account, together with the interests of the organization. This will contribute to enhancing the economic interaction of the national economies of the EAEU members and to strengthening the integration potential of the EAEU, which in the context of increasing geopolitical tension is especially relevant.